Prevalence of Myopia and Its Associated Risk Factors Among the Medical Students of SMBBMU, Larkana, Sindh, Pakistan - Samo, Aliza; Samo, Rukhsar; Mustafa, Amara; Pirzado, Imran Ali; Khokhar, Aqsa; Siyal, Fahad Jibran (Indus Journal of Bioscience Research, 2024)
Myopia, commonly known as nearsightedness, is a refractive error characterized by difficulty seeing distant objects clearly, Prevalence of myopia has been reported to be increasing worldwide. An increase in myopia frequency poses a threat to the health. The aim of this research is to determine the prevalence of myopia and its associated risk factors among the medical students of SMBBMU, Larkana. A cross sectional Descriptive study was conducted at SMBBMU, Larkana with stratified sampling of 250. The prevalence of myopia was 67.6%. A total of frequency 173(69.2%) were females and with frequency 77(30.8%) were males. Majority of myopic students with a percentage of 38.6% had lens power between 1 to 2D. Final year students had the greatest percentage of myopia, 22.48%. Prevalence of myopia was higher in urban students as compared to rural students. Positive association with reading/studying> 3 hours, indoor work 8 hours and inverse with outdoor activity. More than 63.2% students spent less than 3 hours in outdoor activity. High prevalence of myopia was found among the medical students. The increased use of electronic gadgets, decreased outdoor activity, increased indoor activity, and positive family history were found to be the major associated risk factors.